2018
DOI: 10.1111/his.13646
|View full text |Cite
|
Sign up to set email alerts
|

PD‐1 and PD‐L1 expression in HNSCC primary cancer and related lymph node metastasis – impact on clinical outcome

Abstract: Our results characterise the expression profiles of PD-1 axis proteins in HNSCC which might serve as possible clinical prognostic markers.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

11
63
2

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 78 publications
(76 citation statements)
references
References 31 publications
11
63
2
Order By: Relevance
“…PD‐1 is also considered a marker for exhausted T cells and is often upregulated in CD4 + and CD8 + TILs in various types of cancers 30,31 . CD8 + TILs of human HNSCCs were found to express increased levels of PD‐1 on their surface, 32 and 66% to 79% of patients with SCC had PD‐L1‐positive tumor cells 33–36 . In addition, we previously showed that CD8 + TILs in a mouse SCC model highly expressed PD‐1 and LAG‐3 37 .…”
Section: T Cellsmentioning
confidence: 99%
“…PD‐1 is also considered a marker for exhausted T cells and is often upregulated in CD4 + and CD8 + TILs in various types of cancers 30,31 . CD8 + TILs of human HNSCCs were found to express increased levels of PD‐1 on their surface, 32 and 66% to 79% of patients with SCC had PD‐L1‐positive tumor cells 33–36 . In addition, we previously showed that CD8 + TILs in a mouse SCC model highly expressed PD‐1 and LAG‐3 37 .…”
Section: T Cellsmentioning
confidence: 99%
“…This variance in expression may be due to different sample populations, different preparation methods and the lack of a standardized scoring method for determining positivity. These studies have related PD‐L1 expression levels to clinical–pathological features of the patient and disease (Ahn et al, ; Cho, Yoon, Il, Hong, & Hong, ; Hanna et al, ; Hirai et al, ; Kogashiwa et al, ; Lin et al, ; Maruse et al, ; Oliveira‐Costa et al, ; Satgunaseelan et al, ; Schneider et al, ; Stasikowska‐Kanicka, Wągrowska‐Danilewicz, & Danilewicz, ; Straub et al, ; Troeltzsch et al, ).…”
Section: Clinical Implications Of Pd‐l1 Expression In Osccmentioning
confidence: 99%
“…This may be caused by the upregulation of Tregs in HNSCC, suggesting that CTLA-4 may be involved in some aspect of the antitumor effect. Studies have reported that HNSCC patients exhibiting high PD-L1/PD-1 expression tend to have prolonged survival outcomes and a lower probability of recurrence [52,53]. In addition, our signature was negatively correlated with PD-1, but not PD-L1.…”
Section: Genetic Alterations and Gsea Analysis In The High-risk Groupsmentioning
confidence: 60%